Magnetoactive electrospun hybrid scaffolds based on poly(vinylidene fluoride-co-trifluoroethylene) and magnetite particles with varied sizes; Polymer Engineering and Science; Vol. 62, iss. 5 - Botvin V. V. Vladimir Viktorovich; Surmeneva M. A. Maria Alexandrovna; Mukhortova Yu. R. Yulia Ruslanovna; Belyakova Е. О. Elizaveta Olegovna; Vagner D. V. Dmitry Viktorovich; Chelobanov B. P. Boris Pavlovich; Laktionov P. P. Pavel Petrovich; Sukhinina E. V. Ekaterina Vladimirovna; Pershina A. G. Aleksandra Gennadievna; Kholkin A. L. Andrei Leonidovich; Surmenev R. A. Roman Anatolievich (2022, 2022)
Title screen